(untitled) (مجلة العلوم الشاملة, 2025)
Chemotherapy, a widely used treatment for cancer, is known not only for its immune-suppressing effects but also for triggering various side effects. These include toxic secondary reactions and inflammation, which collectively contribute to a diminished quality of life for patients. This review examines strategies aimed at minimizing the collateral damage caused by chemotherapy. Research suggests that the use of certain medications, antioxidants, and herbal remedies has shown promise in mitigating these adverse effects. The research took the form of a cross-sectional study conducted at Elmegriaf Hospital over a six-month period, spanning August 2024 to March 2025. Prior to commencing the study, approval was obtained from the relevant ethics committee. The project was a collaborative effort between the Department of Pharmacology and the Department of Medical Oncology. Among the 100 patients participating in the study, females comprised the majority, making up 65% (82 individuals) of the group. The highest concentration of patients fell within the 51-60 age range, with 38 individuals, representing 30% of the total sample. Cancer treatments frequently result in notable side effects, which can adversely affect nutritional status and overall quality of life. Acknowledging the importance of addressing this challenge, this review outlines strategies for managing these side effects that healthcare professionals can integrate into their care protocols. Although some methods have demonstrated potential in human studies, they should not be adopted independently by cancer patients without professional oversight. Treatment requires consistent monitoring by a multidisciplinary medical team to ensure safety and effectiveness. Additionally, cultivating trust in healthcare providers plays a crucial role in facilitating the safe use of complementary care approaches in conjunction with established supportive therapies.